2020
DOI: 10.1038/s42003-020-01483-2
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system impairs macrophage lipid metabolism to promote age-related macular degeneration in mouse models

Abstract: Metabolic syndrome, a condition involving obesity and hypertension, increases the risk of aging-associated diseases such as age-related macular degeneration (AMD). Here, we demonstrated that high-fat diet (HFD)-fed mice accumulated oxidized low-density lipoprotein (ox-LDL) in macrophages through the renin–angiotensin system (RAS). The ox-LDL-loaded macrophages were responsible for visual impairment in HFD mice along with a disorder of the retinal pigment epithelium (RPE), which is required for photoreceptor ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
3
16
0
Order By: Relevance
“…ERG recording was performed as previously described 20 22 . Briefly, mice were dark-adapted for 12 h and placed under dim-red illumination until they were anesthetized.…”
Section: Methodsmentioning
confidence: 99%
“…ERG recording was performed as previously described 20 22 . Briefly, mice were dark-adapted for 12 h and placed under dim-red illumination until they were anesthetized.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, mitochondrial dysfunction is also deeply involved in AMD [ 2 , 3 ], which is caused by the RPE dysregulation through inflammatory signaling [ 15 , 16 ] and resulting epithelial-mesenchymal transition (EMT) [ 17 , 18 ]. However, the relationship between mitochondrial functions and EMT in the RPE is still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Montserrat-De La Paz et al found that oxidative stress and chronic inflammation were induced in RPE cells exposed to dietary fat, particularly SFA [24]. In animal experiments, Nagai et al demonstrated that high-fat diet-fed mice accumulate abnormal lipid deposition in the RPE, resulting in visual impairment, and have been used as an AMD model [25].…”
Section: Discussionmentioning
confidence: 99%